Correction: A novel and actual mode for study of soil degradation and transportation of difenoconazole in a mango field. Issue 34 (20th June 2019) - Zhao, Fangfang; Liu, Jingkun; Xie, Defang; Lv, Daizhu; Luo, Jinhui
Abstract : Correction for 'A novel and actual mode for study of soil degradation and transportation of difenoconazole in a mango field' by Fangfang Zhao et al., RSC Adv., 2018, 8, 8671–8677.